Better Students Ask More Questions.
Natural Logarithmic Equation ln (x-1) - ln x = ln 49
1 Answer | add yours
The equation ln (x-1) - ln x = ln 49 has to be solved.
Use the property ln x - ln y = ln(x/y)
ln (x-1) - ln x = ln 49
=> ln((x - 1)/x) = ln 49
(x - 1)/x = 49
=> x - 1 = 49x
=> 48x = -1
=> x = -1/48
But the logarithm of a negative number does not exist.
The equation has no solution.
Posted by justaguide on April 23, 2013 at 5:29 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.